Impact of COVID-19 on maternal lifestyle and mother–newborn bonding - Ramos Rodríguez, Anghela (2021)
Introduction: mothers with newborn children became an easy target of the COVID-19 pandemic, their lives today revolve around avoiding its contagion and spread due to the confinement in which they live. Objective: determine the impact of COVID-19 on the relationship between lifestyle and the bond of mother-newborn attachment in a Hospital in Peru. Methods: an explanatory, descriptive-correlational, cross-sectional design was carried out, with a population of 1020 puerperal women and a sample of 103 puerperal women. The sampling was stratified by the presence or absence of COVID-19 in puerperal women. The variables were lifestyles, described by: practice of physical activity, quality of life, rest and sleep, physical health and social integrity, and bonding mother-newborn. Spearman's correlation, discriminant analysis and Wilcoxon's test were used. Results: in both groups of puerperal women made up of 51 with COVID-19 and 52 without COVID-19, the lifestyles were regular (66.7% and 55.8 %), good bonding mother-newborn (64.7%) and regular (55.8 %), intense (62.7 %) and moderate (61.5 %) physical activity, healthy diet (84.3% and 69.2 %), adequate rest and sleep (54, 9 % and 75.0 %), good (62.7 %) and fair (63.5 %) mental health and self-esteem, and high (68.6 %) and medium (67.3 %) social integration. Conclusions: COVID-19 had a significant impact (p <0.05) on the relationship between lifestyles and the bond of maternal attachment with the newborn, with rest and sleep being a determining factor of the impact of COVID-19.